Hubungan Riwayat BBLR Dengan Kejadian Stunting Di Tk Insan Karima Tahun 2022 - Daini Zulmi; Rika Fitriyani; Umul Bahriah (Prodi DIII Kebidanan La Tansa Mashiro, 2023)
Stunting is a growth disorder that occurs due to chronic malnutrition or chronic infectious disease in infants/children under five years old, characterized by a z-scores of less than -2SD/standard deviation (stunted) and less than -3SD (severely stunted). Body weight at birth is one of the indicator in a child's growth and development into adulthood and describes the nutritional status of the fetus during its nutritional status obtained by the fetus while in the womb. the womb. LBW is a low birth weight of less than 2,500 grams, regardless of gestation period. Prevalence data for toddlers WHO stunting prevalence data, Indonesia is included in the third country with the Southeast Asia/South-East AsiaRegional (SEAR), the prevalence of stunting in Indonesia is 24.4%. Based on SSGI data, in 2021 the prevalence of stunting in Banten was 24.5 percent and in 2022 the prevalence of stunting fell to 20 percent, a decrease of 4.5 percent compared to 2021. The prevalence of stunting in Lebak District, Banten Province, is still high, at 26.2% according to SSGI in 2022. This study is an analytic descriptive study. The research design was cross sectional. A total of 86.0% of children who were not stunted with a history of normal birth weight, as many as 95.5% of children were stunted with a history of LBW. the results of the study obtained p value = 0.007 ≤ 0.05, so there is a relationship between birth weight history and the incidence of stunting at Insan Karima Kindergarten in 2022.